Aplicación de narrativa transmedia para la conservación del río el nacimiento del cantón Santa Rosa, año 2021 - Pardo Honores, Kimberly Gabriela; Tinoco Jiménez, Tania Mishelle (Machala, 2022)
The Valley of Life is a transmedia narrative proposal for the conservation of the Nacimiento river in the Valle Hermoso area of the city of Santa Rosa, with the objective of promoting awareness and the importance of preserving the river, as well as involving the state of the other rivers in the city so that people are informed of the seriousness of the problem that is occurring in the canton. In the Valle Hermoso sector, the nacimiento river is a source that is vulnerable to the acts that people carry out without being aware of the consequences that it could have, likewise, the tributaries that are found around the Nacimiento river are in a deplorable state since the contamination of rivers in the city is critical, There is no incentive or project that generates the interest of the citizens to become aware of this problem, which is why we decided to carry out the project for the conservation of the river El Nacimiento and to generate awareness among all the people of the canton of Santa Rosa so that they can take care of all the rivers, especially the river El Nacimiento. It is worth mentioning that the project was approached with key objectives for a good implementation and to raise awareness among the people of Santa Rosa. Firstly, to design narrative worlds from the civic imagination, to develop communication products for implementation on the chosen platforms, and finally, to analyse people's interaction with the transmedia proposal. In order to carry out the objectives, the respective research methodology was carried out by means of data collection through interviews, participatory observation, focus group, therefore, within the research process, professionals in the area of transmedia narrative, graduates in narrative projects, authorities, defenders of the rivers of the Santa Rosa canton, inhabitants of the sector, long-lived characters and people who have visited the river (tourists) participated in the research process. After several results of the data collection from different people, it was possible to name the narrative as "The valley of life", which refers to the illusion of each of the inhabitants that make up the Valle Hermoso site, where they adore and wish for the conservation of the river, which is why within the proposal 4 narrative worlds were established, where through them different realities that occur today in the rivers are told. The first narrative world called "Moments" is characterised by the good times people have in the rivers, fun, peace, joy and different emotions generating good experiences achieved in the river. The second world called "Sad journey", shows the reality of the different rivers showing a contrast from the cleanest river to the polluted river. The third world "The last drop", within this narrative world the opinion of several river defenders is promoted, and the last world called "Your conscience", is significant because it presents all the news issued at National and Cantonal level, shown in a short video, to generate awareness in society. However, to achieve the sharing of the 4 narrative worlds, different communicational pieces were made that helped to expand and attract many citizens of the canton and residents who are outside the country, through: photos of the memory, 360° photo, podcast, short videos, photos, videos, interviews and infographics, different products mentioned above were disseminated through the different platforms selected such as: Facebook, blog and Anchor FM. Based on all the chapters raised, it is possible to show how satisfactory the project was through the statistics exposed by the different platforms Fanpage Karma, Ancho FM and blog, it is worth mentioning that the publications lasted a period of 17 days, achieving a reach of 10,826 people with an engagement of 14% in the social network Facebook analysed through Fanpage Karma, also, the results of Anchor FM gave a total of 17 unique listeners and 20 clicks of reproductions, as for the blog gave a total of 34 visits. However, it is possible to add the prosumers who successfully contributed to the brand, through photos taken by themselves, as well as the shared publications, one or another message demonstrating their participation in each of the implemented publications. The transmedia narrative managed to make several people realise the reality through the different worlds told in small stories, where it allows to generate a change for a much better society, it was possible to fulfil each of the objectives set, it was shown that there are people who want the conservation of the river "El Nacimiento" and also to improve the other rivers.
El Valle de la vida es una propuesta de narrativa transmedia para la conservación del río Nacimiento del sitio Valle Hermoso de la ciudad de Santa Rosa, con el objetivo de promover la concientización e importancia de preservar el río a su vez también involucrar el estado de los otros ríos de la ciudad para que las personas se informen de la gravedad del problema que se está suscitando en ese cantón. En el sector Valle Hermoso el río nacimiento es una fuente que se encuentra vulnerable hacia los actos que personas realizan sin estar conscientes de las consecuencias que podría tener, asimismo, los afluentes que se encuentran alrededor del río el Nacimiento se encuentran en un estado deplorable ya que la contaminación de ríos en la ciudad es crítica, no existe un incentivo o algún proyecto que genere el interés de los ciudadanos para que tomen conciencia sobre aquel problema, es por ello que decidimos realizar el proyecto para la conservación del río El Nacimiento y generar conciencia a todas las personas del cantón Santa Rosa para que puedan cuidar todos los ríos, sobre todo al río El Nacimiento. Cabe mencionar que el proyecto se abordó con objetivos claves para una buena implementación y lograr fomentar conciencia a los santarroseños. En primer lugar, diseña mundos narrativos desde la imaginación cívica, desarrollar productos comunicacionales para la ejecución en las plataformas escogidas, por último, analizar la interacción de las personas con la propuesta transmedia. Para llevar a cabo los objetivos se realizó la respectiva metodología de investigación mediante recolección de datos a través de entrevistas, observación participativa, grupo focal, por lo tanto, dentro del proceso investigativo participaron profesionales en el área de narrativa transmedia, tituladas en proyectos de narrativas, autoridades, defensores de los ríos del cantón Santa Rosa, moradores del sector, personajes longevos y personas que han visitado el río (turistas). Después de varios resultados de la recolección de datos a diferentes personas se logró dar el nombre a la narrativa como “El valle de la vida”, que se refiere a la ilusión de cada uno de los habitantes que conforman el Sitio Valle Hermoso, donde adoran y desean una conservación para el río, es por ello que dentro de la propuesta se establecieron 4 mundos narrativos, donde a través de estos se cuentan diferentes realidades que se da hoy en día en los ríos. El primer mundo narrativo llamado “Momentos”, se caracteriza por los buenos momentos que pasan las personas en los ríos, diversión, paz, alegría y diferentes emociones generando así buenas experiencias logradas en el río. El segundo mundo llamado “Triste recorrido”, aquí se muestra la realidad de los diferentes ríos mostrando un contraste desde el río más limpio hasta el río contaminado. El tercer mundo “La última gota”, dentro de este mundo narrativo se fomenta la opinión de varios defensores de los ríos, y el último mundo llamado “Tú conciencia”, es significativo ya que se presenta todas las noticias emitidas a nivel Nacional y Cantonal, mostrado en un video corto, para que genere conciencia en la sociedad. Sin embargo, para lograr compartir los 4 mundos narrativos se realizaron diferentes piezas comunicacionales que ayudaron a la expansión y atracción a muchos ciudadanos del cantón y residentes que se encuentran fuera del país, mediante: fotos del recuerdo, foto 360°, podcast, videos cortos, fotos, videos, entrevistas e infografías, diferentes productos antes mencionados se difundieron a través de las distintas plataformas seleccionadas como: Facebook, blog y Anchor FM. Con base en todos los capítulos planteados se logra evidenciar cuán satisfactorio resultó el proyecto mediante las estadísticas expuestas por las diferentes plataformas Fanpage Karma, Ancho FM y blog, cabe mencionar que las publicaciones duraron un período de 15 días, logrando un alcance de 10,826 personas con un compromiso del 14% en la red social Facebook analizado por medio de Fanpage Karma, asimismo, los resultados de Anchor FM se dio un total de 17 oyentes únicos y 20 clics de reproducciones, en cuanto al blog dio un total de 34 visitas. No obstante, se logra sumar los prosumidores que aportaron de manera exitosa a la marca, mediante fotos tomadas por ellos mismos, además las publicaciones compartidas, uno que otro mensaje demostrando su participación en cada una de las publicaciones implementadas. La narrativa transmedia logró que varias personas se dieran cuenta de la realidad por medio de los diferentes mundos contados en pequeñas historias, donde permite generar un cambio para una sociedad mucho mejor, se logró cumplir cada uno de los objetivos planteados, se evidenció que si existen personas que quieren la conservación del río “El Nacimiento” y también mejorar los otros ríos.
Keywords: NARRATIVA TRANSMEDIA; IMAGINACION CIVICA; EL NACIMIENTO; VALLE